Zonisamide for neuropathic pain in adults - Moore, R Andrew (Cochrane Database Syst Rev, 2015)
BACKGROUND: Antiepileptic drugs have been used in pain management since the 1960s; some have shown efficacy in treating different neuropathic pain conditions. The efficacy of zonisamide for the relief of neuropathic pain has not previously been reviewed. OBJECTIVES: To assess the analgesic efficacy and associated adverse events of zonisamide for chronic neuropathic pain in adults. SEARCH METHODS: We searched the Cochrane Central Register of Controlled Trials (CENTRAL) (via CRSO), MEDLINE, EMBASE, and two clinical trials databases (ClinicalTrials.gov. and the World Health Organisation Clinical Trials Registry Platform) to 1 August 2014, together with reference lists of retrieved papers and reviews. SELECTION CRITERIA: We included randomised, double‐blind studies of at least two weeks' duration comparing zonisamide with placebo or another active treatment in chronic neuropathic pain. Participants were adults aged 18 and over. We included only full journal publication articles and clinical trial summaries. DATA COLLECTION AND ANALYSIS: Two review authors independently extracted efficacy and adverse event data, and examined issues of study quality. We considered the evidence using three tiers. First tier evidence derived from data meeting current best standards and subject to minimal risk of bias (outcome equivalent to substantial pain intensity reduction, intention‐to‐treat analysis without imputation for dropouts; at least 200 participants in the comparison, 8 to 12 weeks duration, parallel design); second tier evidence derived from data that failed to meet one or more of these criteria and were considered at some risk of bias but with adequate numbers in the comparison; and third tier evidence derived from data involving small numbers of participants that were considered very likely to be biased or used outcomes of limited clinical utility, or both. We planned to calculate risk ratio (RR) and numbers needed to treat (NNT) and harm (NNH) for one additional event using standard methods expected by The Cochrane Collaboration. MAIN RESULTS: We included a single study treating 25 participants (13 zonisamide, 12 placebo) with painful diabetic neuropathy over 12 weeks. No first or second tier evidence was available for any outcome. The small size of the study and potential major bias due to a high proportion of early study withdrawals with zonisamide precluded any conclusions being drawn. There were two serious adverse events (one death) in zonisamide‐treated participants, which were apparently not related to treatment. AUTHORS' CONCLUSIONS: The review found a lack of evidence suggesting that zonisamide provides pain relief in any neuropathic pain condition. Effective medicines with much greater supportive evidence are available.